THE CIVIL SERVICE COMMISSION (CSC) AND SOUND EMPLOYMENT RELATIONS IN ZIMBABWE’S MINISTRY OF PRIMARY AND SECONDARY EDUCATION, MUTARE DISTRICT FROM 2012 TO 2016 - Alouis Chilunjika; Mildred Mahapa; Thabang G. Mofana; Moliehi Mokhothu (CV. RADJA PUBLIKA, 2024)
The study evaluates the role played by the Civil Service Commission in promoting sound employment relations in Zimbabwe’s public sector specifically at the Ministry of Primary and Secondary Education in the Mutare District from 2012 to 2016. The article delves on the nature of the Civil Service Commission, employment relations, the role of the CSC in promoting sound employment relations among a multiplicity of issues. The research explored the functions of the CSC and the challenges it is facing in the promotion of sound employment relations in Zimbabwe’s educational sector. The study relied on the mixed methods approach hence it incorporated qualitative and quantitative methods in the selection of the participants, data collection and data analysis. The findings of the research study indicated that Zimbabwe has not fully managed to promote sound employment relations in the Ministry of Primary and Secondary Education as it faces a myriad of challenges which include: political instability and economic decay, delays in service delivery, mismanagement of public funds and abuse of office. To address the identified challenges the study recommended the comprehensive adoption of noble corporate governance practices in the public sector and the privatization of the CSC in order to cease the government’s intervention in its processes.